Les Pertes Economiques Dues A L’anthracnose De L’anacardier Au Bénin - Houndahouan, Dénis E. Tonon; Zannou, Afio; Sikirou, Rachidatou; Adomou, Aristide; Zinsou, Valérien; Boukari, Sharif; N’djolossè, Kouami (European Scientific Journal, ESJ, 2018)
Anthracnose caused by Colletotrichum gloeosporioides is a disease that causes losses of cashew production in Benin. This study aims to evaluate the economic losses in cashew nuts caused by the disease. The data were collected using a questionary on a sample of 84 farmers from 12 villages in Savè (Centre of Benin) and 126 farmers from 13 villages in N’Dali (North of Benin). These data included socio-demographic characteristics of the respondent, anthracnose expression, disease management methods, yield losses, cashew nut yield, and sale price per kg of cashew nuts. In Savè and N’Dali, 98.68% and 100% of farmers, respectively, reported the presence of anthracnose in their plantations. The yield losses were 316.95 kg/ha (72.19%) at Savè and 189.01 kg/ha (54.71%) at N’Dali. In the period of low demand, these losses amounted an average of 68061 FCFA/ha/farmer at Savè and 42316 FCFA/ha/farmer at N’Dali, while in the high demand periods, they were evaluated to 221576 FCFA/ha/farmer and 135339 FCFA/ha/farmer at Savè and at N’Dali, respectively.